(3GdGKfG YTQjI aj GdMLs - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg Ydi BdGFg (B... (3gPg QSGdI GKfG YTQjI JJdh Ydjc efGSc ML GdJeJY Ydi fgL bQjH (B... (3TQhW hLhH GdML GKfG YTQ, GdHdhZ bHd GdJdHS Hg Ch HYOg bHd CMO Gdehbajf, GdYbd cPGs
(3BNQgG (B:s
(3BNQgG(B: (3Ke hVY GdNO GdCjSQ Ydjg SGFdG ef Gddg HMbg hMb GdbQBf Cf jLYdg ef Cgd TaGYJg (B. (3UdGI QcYJj GdRjGQI YfO GdQCS eSJbHdG GdbHdI Ch GdVQjM GdebOS HTQW YOe GSJdRGe GSJOHGQgG hjOYj HYOgG HGdeGKhQ hjbQC TjFG ef GdbQBf hjgOjg Edi UGMH GdVQjM (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B1: 82s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis